Validation of a food frequency questionnaire to assess dietary cholesterol, total fat and different types of fat intakes among Malay adults - Eng, Jui Yee; Moy, Foong Ming (Asia Pacific Clinical Nutrition Society, 2011)
Background: Cardiovascular diseases are the major cause of death in Malaysia. Evidence shows that dietary fat intake is one of the important risk factors for cardiovascular disease. However, studies assessing the association of fatty acids and risk of cardiovascular diseases in Malaysia are scarce. Therefore, this study aimed to develop and validate a food frequency questionnaire (FFQ) assessing total fat and different types of fat among Malay adults in Malaysia. Methods: A 100 food item FFQ focused on dietary cholesterol, total fat, saturated fat, monounsaturated fat and polyunsaturated fat intake for the past one month was developed and validated against 3-day dietary record (DR) among 151 Malay participants. Validity was assessed through the reliability and agreement of two methods. Intra-class correlation (ICC) coefficients were used to assess reliability; while regression analysis and classification into categories were used to assess agreement of the two methods. Results: The mean nutrient intakes tended to be higher in FFQ compared to DR. The developed FFQ showed excellent reliability with ICC coefficients ranging from 0.92-0.98. Regression analysis demonstrated an acceptable agreement between FFQ and DR for total fat and different types of fat intakes. There were a relatively high proportion of subjects being correctly classified (into same or adjacent category) and only a small number of grossly misclassification for total energy, fat, dietary cholesterol, saturated fat and unsaturated fat occurred. Conclusion: This FFQ is valid in assessing absolute total energy, total fat and types of fat intakes among Malay adults.